Are Students With Disabilities Accessing the Curriculum? A Meta-Analysis of the Reading Achievement Gap Between Students With and Without Disabilities. (April 2019) - Gilmour, Allison F.; Fuchs, Douglas; Wehby, Joseph H.
Federal policies have aimed to improve access to grade-level curriculum for students with disabilities (SWD). Current conceptualizations of access posit that it is evidenced by students' academic outcomes. In a meta-analysis of 180 effect sizes from 23 studies, we examined access as outcomes by estimating the size of the gap in reading achievement between students with and without disabilities. Findings indicated that SWDs performed 1.17 standard deviations, or more than 3 years, below typically developing peers. The reading gap varied by disability label but not by other student and assessment characteristics. We discuss implications for access to grade-level curriculum and potential reasons for why the achievement gap is so large despite existing policies.